Molecular determinants of platelet delta storage pool deficiencies: an update. (1st October 2012) - Masliah‐Planchon, Julien; Darnige, Luc; Bellucci, Sylvia
Summary Delta storage pool deficiency (δ‐SPD) is a rare heterogeneous group of platelet disorders characterized by a reduction in the number or content of dense granules. δ‐SPD causes a mild to moderate bleeding diathesis characterized mainly by mucocutaneous bleeding. Currently, no specific treatment is available and the therapeutic approach is based on prevention of excessive bleeding. However, during the last few years, important insights into the pathophysiology of δ‐SPD have been achieved using mouse models and dense granule deficiency‐associated congenital diseases, such as Hermansky–Pudlak syndrome and Chediak–Higashi syndrome. It thus appears that δ‐SPD represents a genetically heterogeneous group of intracellular vesicle biogenesis and/or trafficking disorders. This review summarizes recent data regarding the molecular mechanisms together with clinical features of the different types of δ‐SPD. Although the molecular basis of isolated inherited δ‐SPD remains currently unknown, next‐generation sequencing strategies should enable researchers to identify the causative genes. Identification of those genes should contribute to our understanding of the pathophysiology, represent useful tools for genetic diagnosis, and eventually lead to new specific therapeutic approaches.